Progress in Mechanistic Research and the Use of Traditional Chinese Medicine in Treating Malignant Pleural Effusion - Gong F; Cheng Y; Li Y; Fan Q; Qu R; Fan T; Lv Y; Dai J (Cancer Management and Research, 2025)
Fengying Gong,1,2 Yunshui Cheng,1 Yongchun Li,1 Qin Fan,3 Rongmei Qu,4 Tingyu Fan,4 Ying Lv,1 Jingxing Dai4 1Department of Traditional Chinese Medicine, Nanfang Hospital of Southern Medical University, Guangzhou, 510515, People’s Republic of China; 2The Second Clinical College of Guangzhou University of Chinese Medicine, Guangzhou, 510405, People’s Republic of China; 3School of Traditional Chinese Medicine, Southern Medical University, Guangzhou, 510515, People’s Republic of China; 4Guangdong Provincial Key Laboratory of Medical Biomechanics and Guangdong Engineering Research Center for Translation of Medical 3D Printing Application and National Key Discipline of Human Anatomy, School of Basic Medical Sciences, Southern Medical University, Guangzhou, 510515, People’s Republic of ChinaCorrespondence: Jingxing Dai, Email daijx@smu.edu.cn; daijx2013@163.com Ying Lv, Email lvying1966@163.comAbstract: Malignant pleural effusion (MPE) is characterized by the accumulation of fluid in the chest cavity, secondary to metastasis from a primary pleural tumor or malignant neoplasms originating from other anatomical sites. MPE is associated with a poor prognosis. Consequently, timely and effective prevention and management of MPE are critical. In Western medicine, the treatment of MPE primarily involves procedures such as surgical puncture for drainage, pleural fixation, chemotherapy, and targeted therapy. In contrast, traditional Chinese medicine (TCM) offers therapeutic modalities including oral decoctions, thoracic perfusion with herbal injections, topical applications of medicinal pastes, and acupoint therapies. The TCM approaches have demonstrated satisfactory clinical outcomes. Advances in the study of TCM for managing MPE in lung tumors are expected to yield a wealth of therapeutic strategies, facilitating the development of more optimized clinical treatments.Keywords: malignant pleural effusion, mechanism, prevention and management, traditional Chinese medicine, lung tumors